1969
DOI: 10.2466/pr0.1969.25.3.679
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Concepts of Masculinity and Femininity

Abstract: Masculinity and femininity as perceived by middle-class American men and women were investigated in two studies. Using adjective checklists and semantic differentials, Ss described most and least masculine and most and least feminine persons. The sexes generally agreed upon the nature of masculinity and femininity. Indices of relationship based upon adjective endorsements indicated that masculinity and femininity are not opposite ends of a bipolar variable; most masculine and most feminine persons have shared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

1972
1972
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 21 publications
5
15
0
Order By: Relevance
“…This is consistent with previous findings (e.g., Jenkin & Vroegh, 1969;Komarovsky, 1946;Wallin, 1950) of persistent gender-role stereotypes. Valian (1998) concludes gender stereotypes still exist and have changed very little over the years.…”
Section: Gender Norms and Stereotypessupporting
confidence: 92%
See 3 more Smart Citations
“…This is consistent with previous findings (e.g., Jenkin & Vroegh, 1969;Komarovsky, 1946;Wallin, 1950) of persistent gender-role stereotypes. Valian (1998) concludes gender stereotypes still exist and have changed very little over the years.…”
Section: Gender Norms and Stereotypessupporting
confidence: 92%
“…Further, they concluded that masculinity and femininity were clearly independent of each other. Jenkin and Vroegh's (1969) second study reinforced the findings of the first study, including a larger sample size. They found that the most descriptive items for LMI were effeminate, emotionally unstable, and an apologetic voice, and the most descriptive items for LFI were arrogant, bossy, and sexually unattractive.…”
Section: Gender Norms and Stereotypessupporting
confidence: 78%
See 2 more Smart Citations
“…Thus to some extent, males and females who hold traditionally feminine expectations in certain areas also tend to hold some masculine expectations. These findings support the conclusions of Vroegh (1971) and Jenkin and Vroegh (1969), who operationalized gender roles as personality traits and focused on different age categories. Their research also challenges the validity of the bipolar and unidimensional nature of gender roles.…”
Section: Relationship Between Gender Role Expectationssupporting
confidence: 89%